Human thermo-physiological comfort assessment in Lisbon by local climate zones on very hot summer days - Reis, Cláudia; Nouri, A. Santos; Lopes, António (Frontiers in Earth Science, 2023)
Extreme heat is a current and future issue on urban areas, with negative impacts on health and quality of life (increasing morbidity and mortality rates). This paper analyses day (12-15h) and nighttime (00-03h) thermo-physiological comfort (TC) conditions by Local Climate Zones (LCZ) in Lisbon during a particular Local Weather Type (LWT), very hot summer days. For this, 13 different microscale sample areas were chosen covering urban and non-urban land cover classes (LCZ 1-3, 4-6, 8, 9, A and B). Universal Thermal Climate Index (UTCI) and Mean Radiant Temperature (MRT) were modeled on SkyHelios for 163 days between 2008 and 2014. Results show that during the day all urban LCZ samples depict the same average TC conditions (mean UTCI of 34ºC – strong heat stress) and densely wooded areas are 2ºC cooler (average UTCI of 32ºC – moderate heat stress). However, compact areas (LCZ 1-3) with lower sky view factor and some vegetation (street trees) display lower percentages of area with higher thermo-physiological discomfort (TD) levels (83% with strong heat stress against 98% in LCZ 8 and 9 and 100% in LCZ 4-6). When considering the hottest days (air temperatures equal or above 35ºC – 75th percentile), the moderate heat stress class disappears in all samples and the very strong heat stress class appears only on urban areas, occupying between 12 to 16% on LCZs 1-3, 10 to 22% on LCZs 4-6, 16 to 22% on LCZ 8 and 9% on LCZ 9. During the nighttime period all samples show no thermal stress, favoring nocturnal physiological recovery. TC conditions in Lisbon are strongly influenced by solar radiation and wind, which explains the need to increase the shading area, preferably by trees, and to promote and preserve ventilation paths.